Rightly Dividing the Word of Truth: Recent Reference Works in Religious Studies - Johnson, Wendell G. (Journal of religious and theological information, 2018)
Several useful multi-volume reference works have been published during the past 2 years. This review essay profiles several of these resources and introduces them to theological librarians and their patrons.